Automatic Nourishing and Watering System Detector for Mint Cultivation - Kurnia Paranita Kartika; Haris Yuana (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
Mint plants provide many benefits in everyday life ranging from enhancing aroma and taste in food and beverages, medicine, perfume, cosmetics until as antibacterial, anti-virus and fungal drugs. Mint is an herbal plant that comes from subtropical areas. When it is planted in tropical areas, mint will grow to creep and will not flowering, so it is cultivated in tropical areas such as in Indonesia by using vegetative methods, namely stem cuttings. This raises problems including shoot growth that takes a long time, regular maintenance, and the need for additional nutrients to support the growth of stems and leaf buds. This study aimed to design and build an automatic integrated care control system for mint cultivation. The integrated system that was built includes the provision of nutrition for young coconut water at a dose of 10 milliliters which is flowed on the surface of the mint plant stem cuttings with the frequency of nutrition twice in a day at 8 AM and 4 PM. The second system that was built was automatic watering carried out on 350 milliliters of mint soil media every morning and evening at 7 AM and 5 PM. After testing, the results showed that the detector could work well in reading the activation time of the nutrient pump and sprinkler pump. There were time differences of 4 milliseconds in the delivery of nutrition testing, while in the delay test for watering the planting medium there was a time difference of 70 milliseconds from the time set on the RTC. Overall, the tools that have been made are adequate to assist farmers in cultivating the mint plant, starting from the process of watering the stem cuttings to providing nutrients to accelerate and increase the growth of leaf buds.Keywords: automatic, humidity sensor YL-69, microcontroller, mint leaves, nourishing system, RTC, watering system.